2012
DOI: 10.7314/apjcp.2012.13.10.5023
|View full text |Cite
|
Sign up to set email alerts
|

Specific CCND1 G870A Alleles Associated with Breast Cancer Susceptibility: a Meta-analysis of 5,528 Cases and 5,353 Controls

Abstract: Background: The Cyclin D1(CCND1) G870A polymorphism may be associated with breast cancer, but the evidence from individual studies is inconclusive. The aim of this study was to investigate the correlation between the CCND1 G870A polymorphism and breast cancer risk in a meta-analysis. Materials and Methods: We searched Pubmed and analysed 11 articles on 5,528 cases and 5,353 controls before February 1, 2012. Results: we found there are significant association for AA versus GG and AA versus GA/GG. No significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 18 publications
(15 reference statements)
2
6
1
Order By: Relevance
“…The symbol filled diamond indicates pooled OR and its 95 % CI increased cancer risk associated with the cyclin D1 polymorphism [46]. Following this, four subsequent meta-analyses were conducted and showed the same results that are consistent with the initial meta-analysis [47][48][49][50]. Conversely, our study is far larger compared with any previous study, implicating an inverse finding.…”
Section: Discussionsupporting
confidence: 82%
“…The symbol filled diamond indicates pooled OR and its 95 % CI increased cancer risk associated with the cyclin D1 polymorphism [46]. Following this, four subsequent meta-analyses were conducted and showed the same results that are consistent with the initial meta-analysis [47][48][49][50]. Conversely, our study is far larger compared with any previous study, implicating an inverse finding.…”
Section: Discussionsupporting
confidence: 82%
“…For example, several meta-analyses studies have reported associations of the CCND1 G870A genetic polymorphism with increased susceptibilities to colorectal, lung, breast, and bladder cancers (Cui et al, 2012;Yang et al, 2012;Zhou et al, 2013;Wang et al, 2014). Notably, while the majority of previous studies observed that the AA genotype contributed to increased cancer risk, for MM, the GG genotype seemed to confer increased risk as reported here and by others (Weinhold et al, 2013).…”
Section: Discussioncontrasting
confidence: 37%
“…In addition to genetic mutations and chromosomal abnormality, a number of single nucleotide polymorphisms (SNPs) in the CCND1 gene such as G870A at the exon 4 splice site were associated with an increased risk and poor prognosis in several types of tumors (Cui et al, 2012;Yang et al, 2012;Zhou et al, 2013;Wang et al, 2014). However, the link between CCND1 SNPs and MM susceptibility is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…This variant may have a longer half-life than the c.723G variant, which may cause the G 1 /S-checkpoint bypass ( 11 ). Published data concerning the association between the c.723G>A polymorphism and the neoplastic process remains inconclusive, although several meta-analyses postulate the presence of a correlation between the c.723A allele and various types of cancers, including breast, gastric, bladder and cervical cancer or squamous cell carcinoma of the head and neck ( 17 20 ). Absenger et al revealed that, in the validation set, the c.723A allele remained significantly associated with a decreased time to tumor recurrence in univariate and multivariate analyses in patients with colon cancer.…”
Section: Discussionmentioning
confidence: 99%